POLICY IMPLEMENTATION ANALYSIS MINIMUM COMPETENCE ASSESSMENT (AKM) IN HASSINA VOCATIONAL HIGH SCHOOL (SMK) SUKABUMI DISTRICT - RIZA WIJAYA SATIVA; R. DENI MUHAMMAD DANIA; UNIN NIBI SAPUTRA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
This research is entitled 'Analysis of Implementation of Minimum Competency Assessment (SMK) Policy in Hassina Vocational High School (SMK), Sukabumi Regency'. This research is motivated by several problems that occur in the implementation of AKM at Hassina Vocational High School, Sukabumi Regency, namely: (1) the occurrence of a digital divide caused by inadequate infrastructure and internet connection speeds that vary between schools and regions (2), the problem of teacher readiness in encouraging students to face AKM, and (3) the problem of student readiness where only 8% of AKM students/participants understand the form of High Order Thinking Skills (HOTS) questions in AKM questions. The purpose of this study is to reveal and understand how the AKM policy is implemented at Hassina Vocational High School, Sukabumi Regency and the factors that can influence the implementation of the policy. The method used in this study is using a descriptive qualitative approach. The theory of policy implementation which is used as an analysis measure consists of 4 dimensions, namely: (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure. The results of this study indicate that Hassina Vocational High School as the implementer of AKM at the education unit level builds good communication with the internal environment and with implementers at the District/City level, and has good human resource availability but in terms of teacher pedagogical competence needs to be improved. As for the commitment of the organizers, school leaders continue to encourage and support the implementation of AKM to run well through improvement and refinement of the bureaucracy both at the policy and technical levels.